(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
This article investigates the petitions sent to the Papal Penitentiary for receiving a declaration that states that the petitioner’s marriage was void. It is well-known that the local ecclesiastical tribunals handled numerous litigations regarding marriages, while such cases brought before the Papal Penitentiary have received less scholarly attention. The study is based on mainly unedited source material gathered from the copybooks of the Penitentiary from the pontificate of the Piccolomini Pope Pius II (1458-1464). The article presents all the existing cases and shows in which kinds of cases Christians from most parts of the Western Christendom have turned to the Penitentiary and asked for the annulment of their marital union. The article argues further that the petitioners might have needed the letters of grace from Penitentiary for a litigation process before an ecclesiastical tribunal.